Encyclopedia of financial models (John Wiley &​ Sons, Inc., 2013)
An essential reference dedicated to a wide array of financial models, issues in financial modeling, and mathematical and statistical tools for financial modeling The need for serious coverage of financial modeling has never been greater, especially with the size, diversity, and efficiency of modern capital markets. With this in mind, the Encyclopedia of Financial Models, 3 Volume Set has been created to help a broad spectrum of individuals-ranging from finance professionals to academics and students-understand financial modeling and make use of the various models currently avai.